EVALUATION OF CLINICAL EXPERIENCE OF IMMEDIATE IMPLANT SUPPORTED REHABILITATION OF EDENTULOUS LOWER JAW WITH PERMANENT PROSTHESIS FIXED ON LESSER AMOUNTOF IMPLANTS. MULTICENTERED CLINICAL TRIAL - R. A. Rozov; V. N. Trezubov; G. S. Azarin (Сеченовский вестник)
The aim of our study is to perform a comprehensive evaluation of our experience of immediate implant supported prosthetic treatment utilising new method TREFOIL indicated in cases of severe atrophy of the lower jaw. 3D planning of the implant supported rehabilitation based on clinical data and X-Ray examination (on CBCT evaluation) was performed in Nobel Clinician software with subsequent immediate placement of 3 implants on lower jaw and concurrent delivery of the ﬁnal prosthesis with standard titanium framework. We applied specially designed Compensation Mechanism to ensure passive ﬁt to the implants. We made time study of the clinical and laboratory stages of treatment, analysed short and long term results of patients rehabilitation. For this concept we used specially designed Nobel Biocare implants with parallel walls and conical connection with the following parameters: diameter - 5.0 mm, length - 11.5/13.0 mm + 4.5 mm. We gained average initial stability torque 38.8 N/cm (from 32 to 47 N/cm) which is sufficient enough for performing immediate loading protocol. Implant and implant supported prosthesis survival rate is 100 %. Average total treatment time is 6.3 hour.